Analysis of Volleyball Players' Physical Condition and Basic Technical Skills at Smandel Padang Club - M Andree Reyhan; Masrun; Yogi Arnaldo Putra; Rudyanto (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to determine the physical condition and basic technical skills of players from the Smandel Padang Volleyball Club. This research employed a quantitative descriptive design. The population consisted of 16 active volleyball players from the Smandel Padang Volleyball Club, and all participants were selected using the total sampling technique. Physical condition was assessed using the bleep test for endurance, the two-hand medicine ball put test for upper-body explosive power, the vertical jump test for lower-body explosive power, and the T-test agility for agility. Basic technical skills were evaluated through serve, Brumbach Forearm Pass Wall-Volley, AAHPER Face Pass Wall-Volley, and smash tests. The results revealed that the players' overall physical condition was classified as fair, while their overall basic technical skills were also classified as fair. These findings indicate the need for structured and continuous training programs, particularly to improve endurance, agility, and attacking skills.